Evidence of innate training in bovine γδ T cells following subcutaneous BCG administration - Samuel, Beulah Esther Rani; Diaz, Fabian E.; Maina, Teresia W.; Corbett, Ryan J.; Tuggle, Christopher K.; McGill, Jodi L. (Frontiers in Immunology, 2024)
The Bacillus Calmette Guerin (BCG) vaccine induces non-specific protection against diseases other than tuberculosis in vaccinated individuals, attributed to the induction of trained immunity. We have previously demonstrated that BCG administration induces innate immune training in mixed peripheral blood mononuclear cells and monocytes in calves. Gamma Delta (γδ) T cells are non-conventional T cells that exhibit innate and adaptive immune system features. In the current study, we determined if BCG administration induced innate immune training in bovine γδ T cells. Sixteen pre-weaned Holstein calves (2-4 d age) were randomly assigned to vaccine and control groups (n=8/group). The vaccine group received two doses of 10^6 colony forming units (CFU) BCG Danish strain subcutaneously, separated by 2 weeks. The control group remained unvaccinated. Gamma delta T cells were purified from peripheral blood using magnetic cell sorting three weeks after receiving the 1 st BCG dose. We observed functional changes in the γδ T cells from BCG-treated calves shown by increased IL-6 and TNF-α cytokine production in response to in vitro stimulation with Escherichia coli LPS and PAM3CSK4. ATAC-Seq analysis of 78,278 regions of open chromatin (peaks) revealed that γδ T cells from BCG-treated calves had an altered epigenetic status compared to cells from the control calves. Differentially accessible peaks (DAP) found near the promoters of innate immunity-related genes like Siglec14, Irf4, Ifna2, Lrrfip1, and Tnfrsf10d were 1 to 4-fold more accessible in cells from BCG-treated calves. MOTIF enrichment analysis of the sequences within DAPs, which explores transcription factor binding motifs (TFBM) upstream of regulatory elements, revealed TFBM for Eomes and IRF-5 were among the most enriched transcription factors. GO enrichment analysis of genes proximal to the DAPs showed enrichment of pathways such as regulation of IL-2 production, T-cell receptor signaling pathway, and other immune regulatory pathways. In conclusion, our study shows that subcutaneous BCG administration in pre-weaned calves can induce innate immune memory in the form of trained immunity in γδ T cells. This memory is associated with increased chromatin accessibility of innate immune response-related genes, thereby inducing a functional trained immune response evidenced by increased IL-6 and TNF-α cytokine production.